Design and modeling of a quasi-zero stiffness isolator for different loads. (1st April 2023) - Zheng, Yawei; Shangguan, Wen-Bin; Yin, Zhihong; Liu, Xiao-Ang
Highlights: An isolator is proposed to acquire QZS characteristics under different loads. An equivalent mechanical model is presented to characterize the proposed isolator behaviors. Experiment validates the proposed isolator is effective for low-frequency vibration isolation under different loads. Abstract: Most quasi-zero stiffness (QZS) isolators are effective to achieve low-frequency vibration isolation for a certain load but are not capable of achieving effective isolation for other loads. In this paper, an isolator composed of n series-arranged elements is proposed to explore the mechanism of acquiring multiple QZS characteristics. Each element of the proposed isolator exhibits a single QZS characteristic under various specific loads, and thus the proposed isolator shows multiple QZS characteristics under different loads. Then, QZS elements are fabricated using Thermoplastic polyurethanes (TPU). Reacted forces of the proposed isolator under static and harmonic excitations are measured. The measurements show that static behavior of the proposed isolator has multiple QZS characteristics, while dynamic behaviors exhibit preload-, amplitude- and frequency-dependent properties. To explore the proposed isolator's properties, three kinds of equivalent mechanical models are proposed. Finally, a single degree of freedom system (DOF) with the proposed isolator is established to investigate its isolation performances theoretically and experimentally. It is found that with the increased layer number, the proposed isolator is effective for achieving low-frequency vibration isolation under various preloads, and this advantage can be enhanced if the damping and excitation are small.